1975
DOI: 10.1088/0034-4885/38/5/002
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced breakdown of gases

Abstract: Powerful flashes of ultraviolet, visible and near-infrared laser light can cause breakdown and plasma formation in gases which are normally transparent at these wavelengths. The ionization processes involved are multiphoton absorption and inverse bremsstrahlung or cascade collisional ionization, in competition with deionization by diffusion, recombination and radiative energy losses. The relative importance of these mechanisms and their roles in leading to the initiation of breakdown and the earliest stages of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
154
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(161 citation statements)
references
References 90 publications
3
154
1
Order By: Relevance
“…Both of these phenomena are treated theoretically by different groups. 7,8 In intense light, an electron can gain sufficient energy by absorbing photons from the radiation field in collision with neutral atoms to produce ionization. The multiphoton ionization process can generate the initial electrons from which an electron cascade can develop, if the laser irradiance is high enough.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these phenomena are treated theoretically by different groups. 7,8 In intense light, an electron can gain sufficient energy by absorbing photons from the radiation field in collision with neutral atoms to produce ionization. The multiphoton ionization process can generate the initial electrons from which an electron cascade can develop, if the laser irradiance is high enough.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Similar gas breakdown phenomena may take place in shock wave ferromagnetic and ferroelectric generators designed with explosively accelerated metallic flyer plates. In fact, in one series of our experiments, we had difficulty obtaining signals from the first of several single-turn diagnostic coils placed along the ferromagnetic element of a FMG.…”
Section: Phys Plasmas 17 074504 ͑2010͒mentioning
confidence: 99%
“…In the early 1960s, it was discovered that the laser beams can induce gas breakdown. 4,5 It was experimentally demonstrated that high-power laser beams cause plasma formation and the propagation of the plasma front in gases with no metallic electrodes in the system. The ionization of gas and the formation of plasma occur due to inelastic collisions between electrons and atoms in which the interaction energy is drawn from the electromagnetic field of the light waves.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of laser-induced breakdown ͑LIB͒ plasma in a gas has been investigated since its discovery 1 resulting in several studies that have been summarized by different authors. [2][3][4][5][6][7][8][9][10][11][12][13][14] The LIB plasma develops a shock wave into the ambient medium and the gas is heated to high temperatures ͑1-3 eV͒. 15 After breakdown, the plasma becomes very opaque and an abrupt shutoff of the laser transmitted light occurs.…”
Section: Introductionmentioning
confidence: 99%